Analysis of the time of provision of outpatient medical record documents at Bhayangkara Hospital in Padang 2019 - Oktavia, Dewi (International Journal Of Community Medicine And Public Health, 2020)
Background: The hospital is a health service institution that plays a role in efforts to improve the degree of public health. One of the important roles in a hospital is the medical recorder installation. One of the minimum service standards for medical records at a hospital is the length of time to provide medical records for outpatient services, which is less than 10 minutes. The purpose of this study was to determine the length of time and to analyze the factors causing the length of time for the provision of medical records for inpatients at Bhayangkara Hospital in 2019. Methods: This research is a combination of research with a sequential explanatory design conducted at the Bhayangkara Hospital in Padang in November 2018 to June 2019. In quantitative research, the sampling technique was by means of the accidental sampling technique and descriptive analysis. While the qualitative research techniques for determining informants were used by purposive sampling and analysis by using content analysis techniques. Results: Quantitative research results, obtained an average time for providing medical records for outpatients is 9 minutes 6 seconds. The qualitative research results obtained that the input of the implementation of the medical record service system is not optimal and the process of implementing the medical record is also not well implemented. Conclusions: The time for providing outpatient medical records is fast according to the minimum hospital medical record service standard, but the implementation is not in accordance with standard operating procedures.